2008
DOI: 10.1071/ea08038
|View full text |Cite
|
Sign up to set email alerts
|

Improving calf survival and performance by supplementation in Bali cattle

Abstract: An on-farm experiment was conducted in several villages in the district of Kupang, East Nusa Tenggara Province (NTT), Indonesia from June to October 2007. The experiment investigated the efficacy of a supplementation strategy to improve calf survival and performance during the dry season. A total of 258 Bali (Banteng, Bos javanicus) cow–calf pairs were used in the experiment. Calves from the 190 cow–calf pairs in the treatment groups were allocated grass hay + concentrate supplementation as follows: 1% (n = 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
8
0
5
Order By: Relevance
“…This is likely to have impacts on their subsequent fertility and calving interval, though this has not yet been shown. High mortality rates and low growth rates of Bali calves have been found in Eastern Indonesia, but this can be improved with grass hay and concentrate (18% CP), but this is expensive and complicated [14] [15]. Forage legumes have the potential as a cheaper alternative to a concentrate ration and preliminary studies have shown similar benefits for calf growth rates.…”
Section: Forage Legumes In Crop-livestock Farming In the Semi-arid Trmentioning
confidence: 95%
“…This is likely to have impacts on their subsequent fertility and calving interval, though this has not yet been shown. High mortality rates and low growth rates of Bali calves have been found in Eastern Indonesia, but this can be improved with grass hay and concentrate (18% CP), but this is expensive and complicated [14] [15]. Forage legumes have the potential as a cheaper alternative to a concentrate ration and preliminary studies have shown similar benefits for calf growth rates.…”
Section: Forage Legumes In Crop-livestock Farming In the Semi-arid Trmentioning
confidence: 95%
“…Teknologi suplementasi langsung pada pedet (pasupet) yang dikembangkan selama ini terbukti secara meyakinkan mampu menekan angka kematian dan sekaligus meningkatkan pertumbuhan dan kualitas bakalan. Mortalitas pedet menurun dari 17,8-35% menjadi di bawah 3% (Jelantik et al, 2008;Copland et al, 2010). Disamping itu, aplikasi pasupet juga melipatgandakan pertambahan berat badan pedet selama periode menyusui , ukuran linier tubuh (Leo-Penu et al, 2008) dan berat sapih dan berat bakalan (Copland et al, 2010).…”
Section: Pendahuluanunclassified
“…Mortalitas pedet menurun dari 17,8-35% menjadi di bawah 3% (Jelantik et al, 2008;Copland et al, 2010). Disamping itu, aplikasi pasupet juga melipatgandakan pertambahan berat badan pedet selama periode menyusui , ukuran linier tubuh (Leo-Penu et al, 2008) dan berat sapih dan berat bakalan (Copland et al, 2010). Hasil kajian selanjutnya juga mencatat bahwa keunggulan pertambahan berat badan pedet tersebut tetap dipertahankan bahkan setelah ternak tersebut tidak lagi mengkonsumsi pakan suplemen (Mullik et al, 2010) dan selama periode penggemukan (Jelantik et al, 2011).…”
Section: Pendahuluanunclassified
“…Skenario di atas sesuai dengan hasil penelitian Jelantik et al (2008) dan , menggunakan suplemen yang terdiri dari pakan lokal berikut ini: jerami rumput alam (10 %), dedak padi (26 %), tepung jagung (35 %), tepung daun lamtoro (15 %), dan tepung ikan (14 %). Semua jenis pakan lokal, kecuali tepung ikan cukup banyak tersedia di tingkat peternak dengan harga yang relatif murah sehingga dengan mudah peternak dapat mengadopsi teknologi pakan tersebut.…”
Section: Upaya Pengendalian Pemotongan Betina Produktifunclassified